Homo Ludens. Games, Fun and People in History - Budzińska, Justyna (Sensus Historiae, 2025)
The article is a discussion of the collective work Replaying the history of entertainment. Historical and archaeological sketches, ed. by M. Michalski, M. Frankiewicz and J. Wojtczak, in the context of the theory of games and plays by J. Huizinga and R. Caillois. The authors of the texts contained in the book analyze various forms of entertainment from antiquity to the present, looking at them in various contexts: ludic, cognitive, educational, upbringing and culture-forming. The wealth of contexts and analyzed forms of entertainment proves that this sphere of human life is not only worthy of research, but also constitutes an inalienable sphere of this life.